Invariant subspaces for products of Bishop operators - Chalendar Isabelle (Acta scientiarum mathematicarum, 2008)
The functional calculus approach of Davie is extended to show the existence of hyperinvariant subspaces for a collection of weighted composition operators that includes certain products of Bishop operators. Moreover it is shown that such operators have trivial point spectrum.